2007
DOI: 10.1096/fj.07-9610com
|View full text |Cite
|
Sign up to set email alerts
|

Methylene blue delays cellular senescence and enhances key mitochondrial biochemical pathways

Abstract: Methylene blue (MB) has been used clinically for about a century to treat numerous ailments. We show that MB and other diaminophenothiazines extend the life span of human IMR90 fibroblasts in tissue culture by >20 population doubling (PDLs). MB delays senescence at nM levels in IMR90 by enhancing mitochondrial function. MB increases mitochondrial complex IV by 30%, enhances cellular oxygen consumption by 37-70%, increases heme synthesis, and reverses premature senescence caused by H2O2 or cadmium. MB also indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
263
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(275 citation statements)
references
References 56 publications
9
263
1
2
Order By: Relevance
“…Similar to the results in a previous study (Atamna et al ., 2008), MB treatment improved normal cell proliferation (Fig. 4A).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Similar to the results in a previous study (Atamna et al ., 2008), MB treatment improved normal cell proliferation (Fig. 4A).…”
Section: Resultsmentioning
confidence: 80%
“…MB is an effective agent to delay cellular senescence at nanomolar concentration and prevent age‐related decline in cognitive function and grip strength (Atamna et al ., 2008; Harrison et al ., 2014). It also exhibits potent antioxidant effects in mitochondria due to its redox property.…”
Section: Resultsmentioning
confidence: 99%
“…It has recently been used in a phase II trial of AD [16]. Furthermore, MB has been reported to have activity as an enhancer of mitochondrial activity [24], and a recent study has reported that it delays cellular senescence in cultured human fibroblasts [25]. However, high doses of MB are known to be toxic and to cause the formation of Heinz bodies in erythrocytes in infants [39].…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized, double-blind, multicenter study with 450 participants with mild-to-moderate AD, Idebenone showed minimal cognitive benefit [69][70][71], but was not approved for treatment of AD based on results not reaching statistical significance in larger trials [70][71][72]. Methylene blue can enhance cytochrome c oxidase activity through direct electron donation [80,81]. In a preclinical AD mouse model, methylene blue treatment reduced Tau-neurofibrillary tangle burden [82].…”
Section: Mitochondrial Bioenergetics As a Therapeutic Targetmentioning
confidence: 99%